Pengaruh Inflasi Nilai Tukar dan BI Rate terhadap Harga Saham pada Perusahaan yang Terdaftar di BEI pada Masa Pandemi Covid-19 - Azizah, Dina Nur; Harahap, Muhammad Nasim (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2023)
This study aims to determine and analyze the effect of Inflation, Exchange Rate, BI Rate on stock prices in companies listed on the IDX during the Covid-19 pandemic. The sampling technique used in this study is to use the pirposive sampling method which aims to obtain samples in accordance with the variables used. The data analysis technique used is descriptive statistical analysis to determine the mean value, maximum and minimum standard deviation on the sample of existing variables, as well as using the classical assumption test, multiple linear analysis, partial hypothesis (T test), simultaneous test (F test). the results of the statistical analysis in this study show that Inflation has a negative effect on stock prices, Exchange Rate has a negative effect on stock prices, BI Rate has a positive effect on stock prices during the Covid-19 pandemic.